Trade re(im)balanced: The role of regional trade agreements - Maria V. Sokolova (Graduate Institute of International and Development Studies, 2016)
This paper documents the novel fact that Regional Trade Agreements (RTA) decrease bilateral trade imbalances as measured by conventional measure of the net export share in gross trade. While on average an RTA decreases bilateral trade imbalance by 7%, greater trade integration through a deeper RTA is associated with a reduction of up to 50% among the sample of over 160 countries since 1960. This implies, that the recent surge in net trade balances has appeared on behalf of the trade between countries that are not involved in RTA integration. The driving channel is the enhancement of cross-border activity and increase in the global value chain integration among RTA members. Overall, this paper implies that the levels of RTA integration should be accounted for in the assessment of aggregate trade balances as the share of GDP, as trade flows bounded by different level of RTA integration will have different reactions to the same shocks. Additionally, I show that RTAs made trade more balanced among its members, and that global increase in the global trade imbalances happened on the expense of the non-RTA trading partners.
Keywords: F10; F13; F14; F15; F40; F41; F45; 330; trade imbalances; regional trade agreements; production integration; economic integration; global value chains